Propuesta de atención de enfermería en el cáncer de mama en el Hospital Oncológico Solca Machala Dr. Wilson Franco Cruz. - Quezada, Tania (2015)
Breast cancer is one of the cancers most often presented in women of our country, an investigation was conducted aimed; Determine nursing care in managing patients with breast cancer in the oncology hospital SOLCA Machala by applying surveys and observation guides for designing a proposal for attention. A descriptive, observational study of cross cohort taking data from the medical records of 238 patients within the variables studied were the application of the nursing process, we used the characteristics of women and own cancer, including for development results; 98% does not meet the nurses with their care based on the SAP, within 2% of problems solved with care process nurse are phlebitis, fever, fatigue, mild dermatitis radio, secondary situations inherent therapy, women who had cancer were those older than 40 years, with a use of more than five years contraceptive methods, having their first birth after age 22, who started one menarche at age 12, the type of cancer in 47.5 is the behavio, 52.2% stage III, undergoing chemotherapy 53.8%, 24.4% metastases. Nurses not comply with a standardized protocol assistance is concluded, it is recommended that nurses are empowered in their professional duties by gestionamiento care.